Cooperative Human Resources Challenges In The Society 5.0 Era - Afiah Mukhtar; Rif’ah Shafwah; Masradin Masradin; Akbar Akbar (Universitas Kristen Indonesia Toraja, 2023)
The challenges faced by cooperative Human Resources (HR) in the era of Society 5.0 are becoming increasingly complex because they require the integration of digital technology with human needs, forcing cooperatives to not only focus on technological progress alone but also on developing their human resources. This research aims to understand in-depth and provide solutions to the challenges faced by cooperative HR. This study uses a qualitative approach with a systematic literature review method and is searched comprehensively using relevant keywords in searches through various online databases. The literature selection process was carried out by considering the reputation of the journal and the recency of the publication (last 5 years) and analyzed in depth using the content analysis method. The conclusion from the research findings is that the challenges for cooperative human resources in the era of society 5.0 are: adaptation to digital technology 5.0 era, cultural transformation, development of new skills, retaining members, collaboration and partnerships the 5.0 era